Effects of plant biostimulants and plant growth regulator applications on plant growth in lilium 'Adelante' - sarı, ömer (Comunicata Scientiae, 2023)
This experiment was designed, it was determined the effects of mycorrhiza, vermicompost, promalin applications on development of plant properties in a bulbous plant, Lilyum 'Adelante. Flower branch length (cm), flower branch diameter (mm), internode number, flower bud number, flower bud length (cm), flower stem length (cm), flower width (cm), flower length (cm), number of leaves and leaf length (cm) were measured. The results showed that no treatment increased plant height more than control plants, but each application had different effects on other plant characteristics. As a matter of fact, mycorrhiza increased internode number, flower bud number, flower bud length, flower stem length, flower length, number of leaves and leaf length by 6.3%, 15.6%, 14.2%, 6%, 40%, 10.3%, 2.9% and 6%, respectively. Vermicompost increased flower bud length, flower length and leaf length by 6.6, 12, 15.3% and 16.1%, respectively. Promalin, on the other hand, increased the flower stem length, flower length and leaf length by 56.3% and 15.4%, respectively. The application of mycorrhiza together with Promalin did not have a different effect than the application of Promalin alone, and even showed a lower effect than the application of Promalin alone. Mycorrhiza, on the other hand, was the application that showed the best effect compared to other applications. Therefore, it can be recommended for plant growth in lilies. However, due to the effect of application time and dose on flowering time, it is possible to obtain different results in plant development in lilies.